Applying theory of constraints to new product development : a knowledge management approach - Shi, Jianyan. (2008)
The primary goal of this research is to establish a foundation for developing an NPD process oriented knowledge management system, which helps to remove the constraints in the process of NPD. Moreover, this research is aimed to unravel the complexity and ambiguity of knowledge with the view of developing a well-structured knowledge management system.